Ethical beliefs and behaviour of university educators: evidence from Russia. (10th March 2021) - Timofeyev, Yuriy; Dremova, Oksana
Abstract : Purpose: This exploratory study aims, firstly, to analyse and categorise judgements on ethical behaviour and actual behaviour of university educators. Secondly, the study addresses the impact of demographic data, such as gender, age and role on these issues. Design/methodology/approach: We utilised online survey data from academic employees of four leading universities in Russia, who are involved in teaching activities. In this study, we used correlation, regression and factor analyses. Findings: Our results demonstrate that teaching, while too distressed to be effective, is a common experience among university educators. By contrast, the rarest categories include teaching under the influence of drugs or alcohol. In addition, there is a high congruence between beliefs and respective behaviours. Females are typically more ethical in both judgements and actual behaviour. Factor analysis of behaviours yielded 16 interpretable factors. Practical implications: Firstly, the salary of the university educators should be adequate and competitive and match with their workload. Secondly, the work of the educators should be given recognition that may become their stimuli for improvement in university teaching. Thirdly, universities should develop ethics centres, which help faculty members and students to take the right decisions in situations involving questionable behaviour in the classroom. Lastly, the development of ethical codes, for faculty members and students, may become their guidance in situations with ethical dilemmas. Originality/value: This study contributed to the very limited research on the ethical aspects of higher education in Russia.